SCIENCE FAIR PROJECT TO IMPROVE 21 CENTURY COMPETENCE (International Conference on Elementary Education, 2018)
The 21st century is characterized by the availability of abundant information, advanced technology, a rapidly changing society, greater convenience in daily lives, and keener international competition. In response to these change, innovation in education is no longer simply encouraged; it has to become an imperative because school are at the front line of this change and need to think about how they can prepare young people for the future workplace. The science fair project is a long-term project where you will plan, conduct, and share results from your own independent investigation. Science Fairs offer students the opportunity to create original scientific research, innovative projects and develop 21st Century learning skills; critical and creative thinking, collaboration and communication The project includes complete the pre-planning steps, conducting a science experiment, recording your data, analyzing your data, and creating a tri-fold poster to share your project. By means of literature study, it obtains the result that the steps done by the students in science fair project are able to improve the ability of 21st century elementary school students.